Antibodies Against the NH2-Terminus of the GluA Subunits Affect the AMPA-Evoked Releasing Activity: The Role of Complement - Cisani, Francesca; Olivero, Guendalina; Usai, Cesare; Van Camp, Gilles; Maccari, Stefania; Morley-Fletcher, Sara; Pittaluga, Anna Maria (Frontiers in Immunology, 2021)
Antibodies recognizing the amino-terminal domain of receptor subunit proteins modify the receptor efficiency to controlling transmitter release in isolated nerve endings (e.g. synaptosomes) indirectly confirming their presence in these particles but also allowing to speculate on their subunit composition. Western blot analysis and confocal microscopy unveiled the presence of the GluA1, GluA2, GluA3 and GluA4 receptor subunits in cortical synaptosomes. Functional studies confirmed the presence of presynaptic release-regulating AMPA autoreceptors in these terminals, whose activation releases [3H]D-aspartate ([3H]D-Asp, here used as a marker of glutamate) in a NBQX-dependent manner. The AMPA autoreceptors traffic in a constitutive manner, since entrapping synaptosomes with the pep2-SVKI peptide (which interferes with the GluA2-GRIP1/PICK1 interaction) amplified the AMPA-evoked releasing activity, while the inactive pep2-SVKE peptide was devoid of activity. Incubation of synaptosomes with antibodies recognizing the NH2 terminus of the GluA2 and the GluA3 subunits increased, although to a different extent, the GluA2 and 3 densities in synaptosomal membranes, also amplifying the AMPA-evoked glutamate release in a NBQX-dependent fashion. We then analyzed the releasing activity of complement (1:300) from both treated and untreated synaptosomes and found that the complement-induced overflow occurred in a DL-t-BOA-sensitive, NBQX-insensitive fashion. We hypothesized that anti-GluA/GluA complexes in neuronal membranes could trigger the classic pathway of activation of the complement, modifying its releasing activity. Accordingly, the complement-evoked release of [3H]D-Asp from antiGluA2 and anti-GluA3 antibody treated synaptosomes was significantly increased when compared to untreated terminals and facilitation was prevented by omitting the C1q component of the immunocomplex. Antibodies recognizing the NH2 terminus of the GluA1 or the GluA4 subunits failed to affect both the AMPA and the complement-evoked tritium overflow. Our results suggest the presence of GluA2 / GluA3-containing release-regulating AMPA autoreceptors in cortical synaptosomes. Incubation of synaptosomes with commercial anti-GluA2 or anti-GluA3 antibodies amplifies the AMPA-evoked exocytosis of glutamate through a complement-independent pathway, involving an excessive insertion of AMPA autoreceptors in plasma membranes but also affects the complement-dependent releasing activity, by promoting the classic pathway of activation of the immunocomplex. Both events could be relevant to the development of autoimmune diseases typified by an overproduction of anti-GluA subunits.